TOWARDS SUSTAINABLE INTEGRATED SOLID WASTE MANAGEMENT IN UNIVERSITY CAMPUS - Yulinah Trihadiningrum (Purifikasi, 2009)
University campuses generate large amount of various types and components of solid wastes. Among the types are municipal solid waste like, laboratory waste, and e-waste. Unfortunately, not many universities have considered the solid wastes as resources. The unseen recovery and recycling potentials of the campus solid wastes has made them to be disposed of without significant reduction efforts. This paper discusses a concept on building-up a sustainable integrated solid waste management in university campus, which covers policy-plan-do-check-action-continual improvement stages. Examples of successful implementation of integrated solid waste management in some universities are also discussed.